“How Do You Communicate The Non-Communicable Diseases?” A Community Empowerment For Sustained Public Health - Sugiyo, Dianita; Adikumoro, Himas Surya; Setyadewi, Winda; Riyadianto, Ridwan; Rahmawati, Indah Septy; Azahra, Masyita; Choiriyah, Nurul; Satria, Faudyan Eka (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Non-Communicable Diseases (NCDs) remain the primary determinant of 36 million mortality occurring worldwide, 29 million of which occurred in developing countries. The study aims to investigate the community involvement on NCDs prevention. This qualitative research, applying a case study method with the structured-data collection and participatory observation and evolving in-depth interviews among stakeholders and a broader community. The secondary data was generated from health status and matrix from related Primary Health Center. This research constitutes the community empowerment as one of the effective NCDs controlling strategies through several initiatives. A local movement which built for raising people’s health status, called Posbindu, which indicates a regular health check, health education by health cadres, and healthy food distribution which made voluntarily by the villagers. A comprehensive communication platform in extending health behavior transformation should evolve the whole community participation. Furthermore, the program’s sustainability should be applied by The National Government.